Nama dan Gelar di Keraton Yogyakarta - Sulistyawati Sulistyawati (Humaniora, 2004)
One of the identities of the Yogyakarta palace community is their names and titles. The naming and entitlement system are influenced by kinship relation, rank in the palace, marital status of the partner of the nobility bearers, previous nobility status, and the working institution. The name and title are given to sultan's family and the abdi dalem (royal servants). There are two types of abdi dalem. The internal abdi dalem (abdi dalem punakawan) are employees who work inside the palace and the external abdi dalem (abdi dalem kaprajan) are those who apply for being "abdi dalem" but they actually work in local governmental offices or other work places. outside the palace. Names can be classified into childhood name and adulthood name, while titles are classified into inherited title and bestowal title. The name and title can be changed. The change of name is usually followed by the change of the title as well. This change can be influenced by age, marital status, and rank.